The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/dsu.12351
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Sentinel Lymph Node Biopsy Compared with that of Breslow Thickness: Implications for Informed Consent in Patients with Invasive Melanoma

Abstract: Sentinel lymph node biopsy may not provide more-accurate prognostic information than Breslow thickness for most melanomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…They found that survival percentage by Breslow thickness falls between the SLNB− and SLNB+ subsets. The prognostic value gained by SLNB in these studies was not useful …”
Section: Sentinel Lymph Node Biopsy and Prognostic Datamentioning
confidence: 76%
See 1 more Smart Citation
“…They found that survival percentage by Breslow thickness falls between the SLNB− and SLNB+ subsets. The prognostic value gained by SLNB in these studies was not useful …”
Section: Sentinel Lymph Node Biopsy and Prognostic Datamentioning
confidence: 76%
“…Freeman et al . performed a meta‐analysis and compared overall 5‐year survival with and without sentinel lymph node stratification.…”
Section: Sentinel Lymph Node Biopsy and Prognostic Datamentioning
confidence: 99%
“…Patients with documented clinical follow-up had allowed correlation analyses of the clinical evolution with the immunocyte infiltration of the SLN or the primary tumor. A recent meta-analysis indicated that primary tumor depth influences the impact of SLN status on OS and represent a better prognostic factor than SLN status [ 28 ]. In individuals with thin melanoma (<1 mm), SLN - status conferred no survival advantage, while for intermediate depths, most studies reported worse survival in SLN + melanoma patients, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Though SLNB identifies patients with microscopic nodal disease, improves regional disease control, 7 and may facilitate the escalation of treatment, it is still controversial whether there is any therapeutic benefit of the procedure, especially in terms of survival. 8-10 In fact, the only randomized-controlled trial (RCT) to evaluate the question of a survival benefit demonstrated no difference in disease-specific survival (DSS) for those treated with SLNB for intermediate-thickness melanoma. 11,12 A criticism of the trial has been that it was under-powered to detect a small but clinically significant survival effect.…”
Section: Introductionmentioning
confidence: 99%